Experimental hatchery designed for the prawn Macrobrachium nipponense in Marine science center, Basrah, Iraq - Al-Maliky, Tariq H. Y.; Ali, Malik H.; Hashim, Amina .A. (Iraqi Journal of Aquaculture, 2021)
This study includes an experimental hatchery design for the oriental river prawn Macrobrachium nipponense from the brackish water of Basrah region (Al-Mashab Marsh). This hatchery consist of five parts: maturation ponds (closed system), hatching of zoug jars, rearing of ponds to larva (nursery and concrete ponds), water tanks and food live of pond (fiberglass). The production capacity was 53,504-190,000 Zoea larvae, 32,355-99,560 Postlarvae. While production of the out ponds (cage two in mud and fiberglass ponds) were estimated between 4,347-24,098 larvae and 2,527-18,828 Postlarvae. Depending on results the total area of the earthen pond and the fiberglass tank, the potential production of Zoea larvae were estimated to be between 36,559-15,300,000 larvae, and between 21,248-11,954,400 Postlarvae. While the total production in all culture systems were 12,600,188-15,760,462 larvae, and between 9,753,349-12,197,630 Postlarvae.